2019
DOI: 10.3390/ijerph16112047
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Assessment of Metals in the Volcanic Soil of Changbai Mountain

Abstract: Tianchi volcano is a dormant active volcano with a risk of re-eruption. Volcanic soil and volcanic ash samples were collected around the volcano and the concentrations of 21 metals (major and trace elements) were determined. The spatial distribution of the metals was obtained by inverse distance weight (IDW) interpolation. The metals’ sources were identified and their pollution levels were assessed to determine their potential ecological and human health risks. The metal concentrations were higher around Tianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…Cr and Ni in the first principal component (PC1) was demonstrated to be derived from parent material and lithogenic sources in many studies [8,21,46]. However, as opposed to other studies [3,5,15,47], Cu in this study was not deemed to have an anthropogenic source; our results are consistent with those of Tian et al [48].…”
Section: Pc1: Cr Cu Nisupporting
confidence: 88%
“…Cr and Ni in the first principal component (PC1) was demonstrated to be derived from parent material and lithogenic sources in many studies [8,21,46]. However, as opposed to other studies [3,5,15,47], Cu in this study was not deemed to have an anthropogenic source; our results are consistent with those of Tian et al [48].…”
Section: Pc1: Cr Cu Nisupporting
confidence: 88%
“…The soil pH in Xiangzhou is in the range of 4.7–7.3, indicating that the cultivated land in the study area is mostly in an acidic environment. The average value concentrations of all PTEs, beyond As and Pb, were underneath the Hubei Province’s background values [ 42 ]. Enrichment factors (EFs) were used to appraise the contamination levels and to assess the level of artificial influence [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is uncommon to find high levels of As and Hg in fish from unpolluted areas, such as in this study. We can tentatively explain this situation considering the geomorphology of the studied site, which showed a derivation from a volcanic eruption that could have led to the release of many metals such as arsenic and mercury (Ma et al, 2019;Witt et al, 2008 number of papers studied the effect of heavy metals on the amount of protein and lipids in fish muscles; only a few data were reported on the correlation between fatty acid of total lipid content and metals accumulation. Khoshnoud et al (2011) reported a study on two fish species of the Persian Gulf, recording a negative correlation with PUFA% for Pb (− 0.507).…”
Section: Discussionmentioning
confidence: 96%